DC-SSCB Snubber for Electric Propulsion Ships With Effective Surge Voltage Reduction and Fast Dissipation of Fault Current Energy - Jae-Hun Cha; Guangxu Zhou; Sung-Geun Song; Feel-Soon Kang (IEEE Access)
This paper proposes a snubber circuit for SSCB that performs voltage clamping operation in two stages to reduce surge voltage. The surge voltage is suppressed in the first stage using a MOV with low operating initiation and clamping voltages. Then, the fault current gradually rises with a gentle slope and reaches the clamping voltage of the second MOV, which shows the effect of reducing the surge voltage. By adding RC circuits connected in series and parallel to two MOVs, fast dissipation of energy generated by fault current, high interrupting capacity, and low energy loss are ensured. Theoretical analysis is performed on the operational mode of the proposed snubber circuit, and its validity is verified through simulation and experiment. The effects of dissipated energy due to fault current, energy dissipation time, surge voltage reduction rate, voltage ringing, and stray inductance are analyzed, and compared with the prior snubber circuit, the proposed snubber circuit is evaluated to be suitable for SSCB of electric propulsion ships.